(untitled) (World Bulletin of Management and Law, 2025)
In the wave of digital transformation, data has become the core production factor that promotes social development . While establishing an information disclosure system, there will inevitably be potential risks of infringement of personal information. Starting with the data obtained from field research, this article analyzes the main challenges currently facing personal information and the contradiction between information sharing and information protection. On the basis of establishing the basic principles of legislation, on the one hand, a sound legal protection system should be established to strengthen supervision; on the other hand, industry self-discipline and personal awareness of information subjects should be strengthened, and efforts should be made to protect personal information from infringement while maintaining the openness and sharing of personal information, so as to find a balance between personal information protection and promoting the free flow of information, and establish an interest balance mechanism between information sharing and personal information protection.